Sistem Pemantauan Kehadiran Piket di Sekretariat Berbasis Algoritma Haversine - Zizilah Kaoy, Muhammad Herbi; Suwandi, Rifki; Pramawahyudi, Pramawahyudi (CHIPSET, 2025)
The lack of discipline in carrying out duty shifts at the student organization secretariat within the Faculty of Information Technology at Andalas University has become a serious issue, characterized by attendance manipulation and absenteeism among members. This problem negatively impacts the operational quality and reputation of the organization. Previous studies on attendance monitoring systems have utilized various technologies, such as RFID and biometric systems, which, while effective in reducing absenteeism, often face challenges in terms of cost, implementation complexity, and manipulation prevention. In response to these limitations, this study developed an attendance monitoring system based on the Haversine Algorithm, utilizing QR code technology for recording attendance and the Haversine Algorithm for monitoring the location of members during their shifts. Testing results indicated that the system achieved 100% accuracy in attendance recording and was able to monitor locations with an average error of 4.657 meters. Compared to previous systems, this approach offers a more cost-effective, easily implementable solution with enhanced transparency and reduced manipulation risk. Additionally, the system provides rapid and transparent attendance reports, with an average response time of 0.1 seconds. In conclusion, the system effectively enhances discipline and reduces attendance manipulation, making it a viable option for improving the management of student organizations.